Estudo de alternativas construtivas para projetos de habitações de interesse social unifamiliares considerando impacto ambiental na tomada de decisão - Bianchi, Pollyanna Fernandes (2021)
The high housing deficit in Brazil contributes to the development of the construction industry. This sector performs an important role in the global economy Evolution, but, besides that, it is responsible for using non-renewable natural resources and to cause environmental damages. In Brazil, there are Social Interest Housing (SIH) programmes to meet the housing deficiency, and it is fundamental that these construction buildings are projected according to the sustainability parameters and that the decision making are not only based on the economic factor. Therefore, this research has the objective to evaluate and select different constructive systems in projects of single-family social interest houses, using the Life Cycle Sustainability Assessment (LCSA) in the decision-making process. Three projects with different construction systems were selected: reinforced concrete with ceramic brick wall, structural mansory and light steel frame, which were selected considering the Life Cycle Assessment (LCA) and the Life Cycle Cost (LCC), combined with thermal comfort and construction time. In addition, the acceptance of the designers and users in front of the different construction systems were considered as a subjective factor. For the projects modelling, the Autodesk Revit software and Tally application for the development of the Life Cycle Assessment (LCA) was used. The selection of the most sustainable project was defined by Analytic Hierarchy Process (AHP) and the range were defined by an online questionnaire. The results indicate that Light Steel Frame (LSF) project presented a better behaviour with the application of the Life Cycle Sustainability Assessment. Besides that, this research concludes that the integration of BIM, LCA and LCC together, in the initial phase of project, contributes to more sustainable houses.